Employment of Social Workers in the Public Sector: Current Situation, Challenges and Future Prospects - kamil Alptekin; Selami Topuz; Murat Öz (Journal of Social Work Education and Practice)
In Turkey, social workers have been working mainly in public sector. However, in the last years, there has been a significant decrease in their employment rates. However, in the last years, there has been a significant decrease in their employment rates. Factors that emerged during the period of uncontrolled growth in social work education such as mushrooming, lacking the standards, explosion in the number of graduates, and decline in the quality of education have been effective in the decline in employment. Apart from these, low levels of professionalization, recognition of other professions, lack of initiative and self-confidence, lack of recognition, and ongoing neoliberalist policies have also played a role in the contraction of employment in the public sector. In order to address the employment issue, there is a need for new and regulatory mechanisms to be put in place in the social work profession and education, which will be built with a common sense that is critically filtered. Social workers should boldly appear in areas that have not yet been officially defined such as school social work, industrial social work, international social work, and take active roles in advocacy, public opinion formation and lobbying activities to address the issue.